Design-curves of strain softening and strain hardening fibre reinforced concrete elements subjected to axial load and bending moments - Varma, R. K. (2012)
Several structural components made by fibre reinforced concrete (FRC) are submitted to axial load and bending moments. In some cases fibres cannot replace completely the conventional reinforcement, even if strain hardening FRC is used; therefore the optimization of the reinforcement solution for these elements depends on the post-cracking behaviour of the FRC, as well as the percentage of conventional reinforcement to replace. To fully exploit the FRC capabilities, the development of a suitable, comprehensive and design-oriented model of its tensile response is of the utmost importance. To provide a practical tool for the pre-design of FRC-structural-elements subjected to axial load and bending moments, design curves were generated using a computational program capable of simulating the main features of the tensile and compressive behaviour of strain softening and strain hardening FRC’s, and steel bars. The post-cracking tensile behaviour of the FRC is characterized by two parameters that define its residual strength ratio (α) and its corresponding tensile strain ratio (β). To generate these curves, a parametric study is carried out based on the tensile parameters α and β and considering distinct mechanical reinforcement ratios, from 0 to 1 with a step of 0.2. For every reinforcement ratio, four distinct cases in terms of β are considered; additionally, for every case of β, α is divided from strain hardening to strain softening in five distinct residual strength classes. By sequentially varying α and β, the bending capacity of a section is evaluated to provide a design perspective of the effect of ductility and strength. The model used in this study is described, the design curves are presented and analyzed and some practical design examples are provided.